The role of educational technologies in CSR perception of tourism education: The comparative analysis of e-learning and m-learning tools as moderators - Basil John Thomas; Tarek Khalil; Nisha Joseph (Journal of Risk and Financial Management, 2020)
The aim of this study is to investigate the effect of educational technologies on the Corporate Social Responsibility (CSR) perception of tourism students and their intention to work in the tourism business industry. By improving education programs with an investment in educational technologies, both universities and firms are believed to benefit from growing CSR initiatives, as well as potential young talents for their future business activities. Four-dimensional (economic, legal, ethical and philanthropic dimensions) model of CSR perception is followed. M-learning and E-learning platforms are compared as moderators to ensure the most effective platform for CSR education among the students. The study is conducted with data which is gathered from a total of 397 students who continue their bachelor and associate degrees in different universities in the Gulf nations. It is found that there is a positive relationship between students' intention to work in the industry and the sub-dimensions of CSR, namely ethical responsibilities, legal responsibilities, and economical responsibilities. Conversely, philanthropic responsibilities had no effect on working intention. In addition, gender difference had no significant impact on working intention of the students in tourism industry. Moreover, it is revealed that e-learning tools are more effective in CSR education.
Keywords: 330; CSR; intention to work; tourism education; e-learning; m-learning